2023
DOI: 10.1002/hep.32692
|View full text |Cite|
|
Sign up to set email alerts
|

HCC EV ECG score: An extracellular vesicle‐based protein assay for detection of early‐stage hepatocellular carcinoma

Abstract: Background and Aims: The sensitivity of current surveillance methods for detecting early-stage hepatocellular carcinoma (HCC) is suboptimal. Extracellular vesicles (EVs) are promising circulating biomarkers for early cancer detection. In this study, we aim to develop an HCC EV-based surface protein assay for early detection of HCC.Approach and Results: Tissue microarray was used to evaluate four potential HCC-associated protein markers. An HCC EV surface protein assay, composed of covalent chemistry-mediated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Probably the closest study to a clinical application is the HCC EV ECG score, an extracellular vesicle-based protein assay for detecting early-stage hepatocellular carcinoma ( 228 ). Here, exosomes isolated from plasma are analyzed for surface expression of EpCAM, CD63, CD147, CD63, and GPC3.…”
Section: Promising New Biomarkers For Clinical Applicationmentioning
confidence: 99%
“…Probably the closest study to a clinical application is the HCC EV ECG score, an extracellular vesicle-based protein assay for detecting early-stage hepatocellular carcinoma ( 228 ). Here, exosomes isolated from plasma are analyzed for surface expression of EpCAM, CD63, CD147, CD63, and GPC3.…”
Section: Promising New Biomarkers For Clinical Applicationmentioning
confidence: 99%
“…Sun N et al developed and optimized an HCC-specific EV surface protein detection method (referred as HCC EV ECG score), based on three HCC EV subpopulations of EpCAM + CD63 + , CD147 + CD63 + , and GPC3 + CD63 + , by which EVs were isolated from peripheral blood, and HCC EV surface proteins were detected. This new established detection model was confirmed to have an accuracy of more than 93% (AUC >0.93) in distinguishing early HCC from cirrhosis with excellent detection performance ( Sun et al, 2022 ). LC3B (MAP1LC3B) is a widely used marker of autophagy.…”
Section: Applications Of Evs In Early Diagnosismentioning
confidence: 86%
“…Extracellular vesicles (EVs) represent another type of "liquid biopsy" holding promise in HCC. As EVs contain DNA, RNA, proteins, metabolites and lipids from both normal and tumor cells and are present in circulation, several studies have investigated their role in detecting HCC among at-risk patients [42][43][44][45] . A recently published phase 2 biomarker study revealed a 91% sensitivity and 90% specificity for distinguishing early-stage HCC from cirrhosis, of which NAFLD represented 20% [46] .…”
Section: Limitations Of Available Surveillance Tools and Potential So...mentioning
confidence: 99%